Developing Transformational Strategies to Improve the Accessibility of E-Governmental Services in South African Local Government - Nkgapele, Simon Matome; Mokgolobotho, Regina Mapula (International Journal of Law, Social Science, and Humanities, 2024)
The access to electronic governmental services is an important element of effective governance, particularly in developing nations such as South Africa, where there are still differences in access and skills to digital technologies. As digital transformation becomes increasingly important for effective governance, it is urgently necessary to develop strategies to ensure that all citizens can access electronic governmental services. This study focused on the development of transformation strategies to enhance access to electronic governmental services in local governments in South Africa. This qualitative research used existing literature and case studies to develop transformation strategies to improve access to digital government services. The paper evaluated how the accessibility of electronic government services affected the responsiveness and effectiveness of the provision of local government services. Moreover, the paper also examined the impact of socio-economic factors on the accessibility of electronic services provided by municipalities in South Africa. This included the assessment of the citizens' perceptions of the use and accessibility of the current electronic government services of the municipalities of South Africa. Finally, although electronic public administration services have great potential to enhance local governance in South Africa, their accessibility depends on a solution to socio-economic imbalances, infrastructure limitations, technological obstacles, and trust issues. The study provided strategies for promoting the access of local government e-government services in South Africa. As a result, the findings of the paper contributed to growing knowledge on e-government tactics to improve service delivery and promote good governance practices in South Africa. Keywords: E-Government Services, E-Government, South African Local government, Accessibility